2002
DOI: 10.1073/pnas.092615399
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the membrane anchor of the target receptor is a mechanism of bioinsecticide resistance

Abstract: The mosquitocidal activity of Bacillus sphaericus is because of a binary toxin (Bin), which binds to Culex pipiens maltase 1 (Cpm1), an ␣-glucosidase present in the midgut of Culex pipiens larvae. In this work, we studied the molecular basis of the resistance to Bin developed by a strain (GEO) of C. pipiens. Immunohistochemical and in situ hybridization experiments showed that Cpm1 was undetectable in the midgut of GEO larvae, although the gene was correctly transcribed. The sequence of the cpm1GEO cDNA differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 28 publications
(32 reference statements)
4
66
1
Order By: Relevance
“…The proposed immune-related tolerance mechanism is different from previously described Bt-resistance mechanisms (3) in which the observed reductions in Bt toxicity are explained almost exclusively in terms of alterations to receptor properties on the gut epithelium (4,5). However, our results in E. kuehniella are consistent with recent observations of malaria-refractory Anopheles gambiae colonies, which have elevated oxidative activities compared with susceptible insects (13,14).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The proposed immune-related tolerance mechanism is different from previously described Bt-resistance mechanisms (3) in which the observed reductions in Bt toxicity are explained almost exclusively in terms of alterations to receptor properties on the gut epithelium (4,5). However, our results in E. kuehniella are consistent with recent observations of malaria-refractory Anopheles gambiae colonies, which have elevated oxidative activities compared with susceptible insects (13,14).…”
Section: Discussionsupporting
confidence: 43%
“…However, despite the use of Bt endotoxins in transgenic crops covering Ͼ11.4 million hectares (2), the precise details of how endotoxins bind to gut cells to kill insects are poorly understood (3). This limitation impedes our understanding of potential mechanisms of insect resistance to Bt endotoxins other than the loss or modification of receptors (4,5), altered proteolysis of protoxin and͞or toxin (6,7), and repair and͞or replacement of damaged cells (8). Although few insect species have developed resistance in the field (3,9), genetic resistance to Bt-endotoxins has been selected in several species in the laboratory (3,10).…”
mentioning
confidence: 99%
“…Bioassays are further limited in that they demand large sample size and maintenance of F1 or F2 progenies in the laboratory and assays should be performed under specific conditions to provide reliable data. In the context of Culex resistance to B. sphaericus, the improvement in DNA screening is needed to track other resistance alleles already described (10,11), since the PCR used in the study is specific for the cqm1 REC allele. The ␣-glucosidade in-gel assay can also be useful to detect individuals not expressing Cqm1 whose resistance can be associated with alleles other than cqm1 REC , although this assay is able to detect only homozygous resistant larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Four cpm1/cqm1 resistance alleles were found in Culex populations of different origins. The cpm1 GEO allele, detected in a C. pipiens laboratory-selected colony (GEO) from California, contains a nonsense mutation leading to the synthesis of a truncated protein lacking the glycosylphosphatidylinositol anchor and is therefore not able to localize to the apical membrane of the midgut epithelium (11,38). A 19-nucleotide deletion in the gene cqm1, here named cqm1 REC , was associated with the resistance of a C. quinquefasciatus laboratory colony (CqRL1/ 2362) originating from the city of Recife (Brazil), and this mutation prevents the expression of Cqm1 on the midgut brush border membranes (28,29,30).…”
mentioning
confidence: 99%
“…In addition, Cyt1A can overcome very high levels of resistance to the Bin toxin of B. sphaericus 2362 when combined with this species (Wirth et al, 2000a) and can extend its target spectrum to A. aegypti (Wirth et al, 2000b). Recent studies using fluorescent dyes have shown that the lack of sensitivity in B. sphaericus-resistant C. quinquefasciatus is due to the absence of the Bin toxin receptor in the midgut microvillar membrane (Darboux et al, 2002). Studies in our laboratory have shown that Cyt1A forms lesions in this membrane that enable the Bin toxin to enter these cells and exert toxicity (Fig.·3).…”
Section: Properties Of Btimentioning
confidence: 99%